Presence of Dengue Antibody in a Newborn with Maternal Peripartum Dengue Fever - Islam, Mohammad Ariful; Hasan, Mehedi; Sharmin, Farzana (Journal of Bangladesh College of Physicians and Surgeons, 2023)
In Bangladesh, the incidence of dengue infection continues to rise, and it has been related to severe maternal and infant morbidity during pregnancy. After presenting with an initial onset of fever at 37 weeks’ gestation, an 18-year-old pregnant woman ended up being diagnosed with dengue fever. The rapidly declining platelet count, 18,000/mm3 on the third day, necessitated a blood transfusion. On day six of her illness, while her platelet count was 23,000/mm3, she developed pre-labor rupture of membranes with labor pain. The labor became prolonged, with signs of obstruction. A prompt caesarian section was carried out under general anesthesia. She was discharged from the hospital on the 4th post-operative day without any negative sequelae. After birth, the newborn was diagnosed with dengue IgG by potential vertical transmission. Early detection and treatment are necessary for dengue during pregnancy. However, physicians must exercise extra caution when treating a pregnant dengue-infected patient by maintaining their physiological state, preventing shock, and, at the same time, taking care of the fetus, which may develop distress. J Bangladesh Coll Phys Surg 2023; 41: 120-122